1984
DOI: 10.1055/s-2007-1023343
|View full text |Cite
|
Sign up to set email alerts
|

Fever, Leucocytosis and Infection after Open Heart Surgery. A Log-linear Regression Analysis of 115 Cases

Abstract: A prospective investigation was undertaken in adults to assess the specificity and sensitivity of fever (greater than 38 degrees C) and leucocytosis (greater than 10 000/microliters) for the diagnosis of infection after operations with cardiopulmonary bypass. A log-linear model analysis of a multiway frequency table was used for statistical evaluation. The model parameters were separately evaluated for 2 periods: the early one until the 6th day, the late period from the 7th postoperative day until discharge. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…One study of 185 patients after cardiac valve surgery demonstrated the unreliability of leukocytosis and fever [4]. Another study noticed that signs of fever and leukocytosis were more frequent in infected patients but only after the sixth postoperative day [5]. Furthermore, these parameters lack speciWcity: only 15% of patients with fever or elevated WBC count after the sixth postoperative day had infection.…”
Section: Discussionmentioning
confidence: 99%
“…One study of 185 patients after cardiac valve surgery demonstrated the unreliability of leukocytosis and fever [4]. Another study noticed that signs of fever and leukocytosis were more frequent in infected patients but only after the sixth postoperative day [5]. Furthermore, these parameters lack speciWcity: only 15% of patients with fever or elevated WBC count after the sixth postoperative day had infection.…”
Section: Discussionmentioning
confidence: 99%
“…The value of serial CRP determinations in postoperative patients who have undergone cardiac surgery is well-established (39)(40)(41). Studies have demonstrated the usefulness of CRP in predicting postoperative infectious complications before the onset of clinical symptoms.…”
Section: Serial Measurementsmentioning
confidence: 99%
“…Postoperative subphre nic abs cesses are complicati ons most frequently observed after abd ominal surgeries (4,5). To our knowledge ther e are no reports of subphrenic absces ses after ca rdiac su rgery .…”
Section: Discussionmentioning
confidence: 93%
“…Sometimes, the paucity of symptoms and signs makes the identification of a subphrenic abscess difficult (4), as occurred in our pati ent. Perop er ative antibiotics may have been resp onsible for suppression of the symptoms (4,5). We hypoth esize that the ab scess was provoked by a lesion of the diaphragm caused by inadequate care in applying the right pleural drainage.…”
Section: Discussionmentioning
confidence: 93%